Distinguishing Rice Genotypes using Morphological, Agronomical, - Susanto, Untung; Rohmah, Nofi Anisatun; Mejaya, Made Jana (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Complete data on characteristics of a rice variety is very important toÂ  race the authenticity of the variety at the field. Sometimes a name of a variety had changed, due to the informalÂ  seed distribution among farmers. This could become problem in the property right of the variety. Distinguishing among rice varieties using only morphological and agronomical traits are sometimes not sufficient. Currently, molecular markers such as SSR (Simple Sequence Repeats) and SNP (Single Nucleotide Polymorphism) markers have become available and are powerfull to distinguish rice genotypes. This research was aimed to distinguish nine rice varieties grown by farmers, using morphological characters (47 traits), agronomical characters (9 traits), SSR markers (12 primer pairs, related with important traits of rice plant), and 384 SNP markers, and to compare the effectiveness of each technique in distinguishing among genotypes. A field experiment was conducted in Ranca Jaya village, Patok Beusi, Subang, West Java during Wet Season (WS) of 2011/2012, using a Randomized Complete Block Design in three replications. A modified CTAB method was used to extract DNA for detection using 12 SSR markers and 384 SNP markers. The results revealed that the use of SSR markers that were linked to certain genes was more accurate than that of the SNP markers, agronomic, and morphological characters, in distinguishing differences among the 9 rice genotypes. The complete data of morphologic, agronomic, and molecular are useful to distinguish the authenticity of a variety in order to protect the intelectual property right attached on the variety.